Design of Reminder Information Last Contract (RILC) Applications Using Web-Based Sms Gateway - Arip Solehudin; Aldi Angga Putra; Kamal Prihandani; Nono Heryana (Buana Information Technology and Computer Sciences (BIT and CS), 2020)
Currently informarsi system is needed by several large companies. To support some data processing, one of them is employee data processing and employee contract data. Given the existing problems in contract data pengelohan often occurs that the check is not maximal so some data left behind and even neglected impact on the increase in salaries of employees who are late due to contracts that are not handled according to schedule. This study aims to create a web-based RIL application using sms gateway for delivery of contract data reminder information. This research uses SDLC method with Extreme Programming model with stages of planning, designing, coding, testing, implementation and evaluation. SMS gateway is a gateway for information dissemination using SMS. With SMS gateway can spread the message of the serial number automatically and quickly which is directly connected with the database of mobile numbers that have been stored. This can be done by RIL applications in sending reminder information messages to the HRD division as well as employees receiving their contract expiration date information. The result of the research is the user can maximize the checking of contract data so that nothing is left behind and give the report that arranged well and clear